PERADILAN TATA USAHA NEGARA PASCA UNDANG-UNDANG ADMINISTRASI PEMERINTAHAN DITINJAU DARI SEGI ACCESS TO JUSTICE - Indra Permana, Tri Cahya (Jurnal Hukum dan Peradilan, 2015)
The Government Administration Act has expanded the access to justice for justice seekers in Administrative Court by opening the "empty spaces" that were not previously accessible for justice seekers. Hence Government Administration Act has opened access to justice, the Judge as the central figure of law enforcement should also committed to changes and developments, including changes and legal developments in the field of Government Administration. Access to justice is a human right that must be guaranteed, not just move the absolute power of the other judicial authority to the Administrative Court. His attempt is to cover the empty space/ vacuum which cannot be filled by the Administrative Court and other courts. The Administrative Court Judge are no longer narrow the authorization of Administrative Court on the pretext object of the dispute is not individual, not final, civil disputes especially since the disputed a declarative decision. The judge would have to implement the content of Government Administration Act along with the Supreme Court Regulation No. 4 of 2015 and the Supreme Court Regulation No. 5 Year 2015. To avoid disagreement of the law, the new law is applied with some implementation strategies that really understood what the intent and purpose of the Government Administration Act, including the rules of procedure. However, if in the Rules of the Supreme Court felt there are things that are not in accordance with the Law or the needs of the practice of the trial, the judge can make an effort constitutional question to the Constitutional Court or temporarily set it aside pending the revision of the Rules of the Supreme Court No. 4 of 2015 and the Supreme Court Regulation No. 5 in 2015.Keywords: Administrative Court, Government Administration Act, Access to Justice